Fundraising as a condition for the development and restoration of domestic enterprises in the post-war period - Olena Lagovska; Олена Лаговська; Gabriella Loskorikh; Лоскоріх Габріелла; Loszkorih Gabriella (II. RFKMF, 2024)
Abstract. One of the most common problems faced by both start-up and experienced entrepreneurs is the lack of or insufficient funds to achieve various business goals. To develop creative business ideas and support small and medium-sized businesses, grant funding is used around the world to help entrepreneurs who can offer important and useful projects for the state. State support programmes for small and medium-sized businesses are primarily aimed at industries that are a priority for the state. The state will help with financing a business that will be useful for a region, oblast, or even a specific city: for example, opening a pharmacy, developing crop production, or tourism [9]. However, the state should not support gambling, alcohol, or cigarette businesses [10; 6]. At the same time, it should be borne in mind that the state has levers to choose, for the purpose of further financing, those projects that can directly or indirectly lead to qualitative transformations in the country's economy, support its image, or create prerequisites for further development.
Фандрайзинг як умова розвитку та відновлення вітчизняних підприємств у поствоєнний період
Fundraising mint a hazai vállalkozások fejlesztésének, valamint helyreállításának feltétele a háború utáni időszakban
Keywords: fundraising; domestic enterprises